FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PEMBACA DALAM MEMPEROLEH INFORMASI GAYA HIDUP SEHAT (Studi kasus Pembaca Tabloid Senior di Kecamatan Bogor Utara) - Endang Sri Wahyuni; Ma’mun Sarma; Ismail Pulungan (Jurnal Penyuluhan, 2007)
Healthy behavior is an important physical and psychological needs for human beings. Therefore, to attain good healthy behavior results, it is essential to study of the process to obtain information oh healthy life style in the Senior tabloid. Objectives of this research are to analyze individual characteristic (internal factors) and external factors (physical environment, social environment, and cultural environment), and to analyze the relationship between the internal factors and external factors and reader behavior. This study is a correlational description research, consists of 40 respondens of Senior tabloid reader were taken as sample. The sampling method was Sensus, and the technique of analysis were Spearman correlation method.The important results are : (1) reader behavior classified of five parts: exertion obtain an information source, reading frequency, reading schedule, exertion to store the information source, and information application, (2) internal factors that have significantly correlate to reder behavior are: job, healthy life style experience, family quantity, and cosmopolit, and (3) external factors that have significantly correlate to reader behavior are: packaging, content (topic and language), self concept, group effect, value system, and social process.